THE REFLECTIONS OF INDIVIDUALISM AND COLLECTIVISM IN AMERICAN AND VIETNAMESE TV ADVERTISEMENTS = Sự phản ánh tính cá nhân và cộng đồng trong quảng cáo truyền hình của Mỹ và Việt Nam - Hoa, Huyền Trang (2020)
Nowadays, with the development of the market, people are possibly approaching different kinds of TV advertisements from both internal and external cultures which are aimed at influencing their attitudes towards a wide range of products. Together with the development of modern multimedia, this spread varies the reflection of cultural characteristics in these TV advertisements. The study focuses on the reflection of Individualism and Collectivism in American and Vietnamese television advertisements. The features of Individualism and Collectivism will be assessed on the previous theories of some famous theorists and researchers. To investigate these cultural reflections, 10 American TV advertisements and 10 Vietnamese TV advertisements were collected. The total number of these 20 commercials was then carefully analyzed in their contents with the application of qualitative methods. At last, remarkable insights into the cultural reflection in television commercials of two cultural groups are figured out as well. Finally, the research offers some suggestions on studying cross – cultural communication for English teachers and learners, providing a useful tool for the study of advertising strategy for American and Vietnamese markets.